The emerging role of neutrophil extracellular traps in fungal infection - Liang, Chuting; Lian, Ni; Li, Min (Frontiers in Cellular and Infection Microbiology, 2022)
Fungal infections are global public health problems and can lead to substantial human morbidity and mortality. Current antifungal therapy is not satisfactory, especially for invasive, life-threatening fungal infections. Modulating the antifungal capacity of the host immune system is a feasible way to combat fungal infections. Neutrophils are key components of the innate immune system that resist fungal pathogens by releasing reticular extracellular structures called neutrophil extracellular traps (NETs). When compared with phagocytosis and oxidative burst, NETs show better capability in terms of trapping large pathogens, such as fungi. This review will summarize interactions between fungal pathogens and NETs. Molecular mechanisms of fungi-induced NETs formation and defensive strategies used by fungi are also discussed.